2012
DOI: 10.1007/s10714-012-1374-z
|View full text |Cite
|
Sign up to set email alerts
|

Test of the weak cosmic censorship conjecture with a charged scalar field and dyonic Kerr–Newman black holes

Abstract: A thought experiment considered recently in the literature, in which it is investigated whether a dyonic Kerr-Newman black hole can be destroyed by overcharging or overspinning it past extremality by a massive complex scalar test field, is revisited. Another derivation of the result that this is not possible, i.e. the weak cosmic censorship is not violated in this thought experiment, is given. The derivation is based on conservation laws, on a null energy condition, and on specific properties of the metric and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 42 publications
6
60
1
Order By: Relevance
“…Assuming only that the non-electromagnetic contribution to the stress energy tensor satisfies the null energy condition, we will prove that for arbitrary processes involving matter falling into an exactly extremal Kerr-Newman black hole, no violation of (1) can occur at linear order in the perturbation. This result, which was previously obtained for charged scalar matter in [17] and generalized in [18], generalizes the results derived for particle matter in paper I [3] to completely general matter.…”
Section: Introductionsupporting
confidence: 88%
“…Assuming only that the non-electromagnetic contribution to the stress energy tensor satisfies the null energy condition, we will prove that for arbitrary processes involving matter falling into an exactly extremal Kerr-Newman black hole, no violation of (1) can occur at linear order in the perturbation. This result, which was previously obtained for charged scalar matter in [17] and generalized in [18], generalizes the results derived for particle matter in paper I [3] to completely general matter.…”
Section: Introductionsupporting
confidence: 88%
“…Both him and subsequent authors [4,5] found that the particle would not go in for values of the conserved quantities (energy, angular momentum, charge and/or spin) which would overspin/overcharge the black hole. Similar conclusions were reached by analyzing scalar and electromagnetic test fields propagating in extremal Kerr-Newman black hole backgrounds [6,7,8,9]. In this case, the fluxes of energy, angular momentum and charge across the event horizon were found to be always insufficient to overspin/overcharge the black hole.…”
supporting
confidence: 60%
“…Extending Wald's calculation further, an analogous result of overcharging a Kerr-Newman black hole in the presence of both electric and magnetic charged was studied in [8]. Overcharging via test field absorption instead of test particle was pursued in [9][10][11]. Various other attempts of overcharging have been carried out in last few decades over a wide range of black hole solutions in general relativity in order to look for any possible violation of cosmic censorship [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%